Eosinophilic Granuloma Syndrome with Conjunctival Involvement: A Case Report - Daryabari, Seyyed Hashem; Javadi , Mohammad Ali; Shams , Majid (Journal of Ophthalmic and Optometric Sciences, 2020)
Abstract To report a rare case of eosinophilic granuloma with bilateral conjunctival involvement. A 27-yearold female patient was referred to our center due to granulomatous lesions in the upper conjunctiva of both eyes, which began about two years ago. Patient also had a history of lung disease (Asthma) from about 7 years ago. The patient was eventually diagnosed as a case of bilateral eosinophilic granuloma of eyes with pulmonary involvement. Treatment with systemic corticosteroid resulted in disappearance of the eye lesions after one month.Although eosinophilic granuloma of eye is a very rare condition it should be considered as a differential diagnosis for eye masses especially in patients with concurrent lung problems.